Respect for Ancestors in the Bau Lolon Riteln Kolilanang Village, Adonara Subdistrict East Flores Regency - Angela Merici Benga Angin; Nurlela (Gudang Jurnal Multidisiplin Ilmu, 2026)
This study examines the Bau Lolon ritual in Kolilanang Village, Adonara Sub-district, East Flores Regency, focusing on its role as a traditional practice of ancestral veneration. The Bau Lolon ritual serves as a sacred medium for the local community to express gratitude, seek blessings, and maintain a spiritual connection with their ancestors. Utilizing a qualitative approach with ethnographic methods, data were gathered through field observations, structured interviews with traditional elders (Tua Adat), and documentation of the ritual steps. The findings reveal that the ritual embodies deep philosophical values, including cosmic balance, kinship solidarity, and cultural identity preservation. Furthermore, the Bau Lolon ritual functions as a social mechanism that strengthens communal bonds among the villagers. Despite modern societal shifts, the people of Kolilanang continuously preserve this ritual, demonstrating a resilient synthesis between ancestral traditions and contemporary community life.